2020
DOI: 10.51594/imsrj.v1i3.68
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Obstetric Danger Signs and Associated Factors Among Pregnant Women Who Attend Antenatal Care in Public Health Institutions of Adama City, Oromia, Ethiopia

Abstract: Improving awareness of women about obstetric danger signs of pregnancy, labor, and postpartum period is the crucial first step in accepting appropriate and timely health care service. In Ethiopia, where pregnancy related complications and maternal death is high, little is known about level of awareness of obstetric danger signs. The aim of this study was to assess Awareness of Obstetric Danger Signs and Associated Factors among Pregnant Women who attend Ante-natal care in Public Health Institutions of Adama Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 12 publications
3
6
3
Order By: Relevance
“…Many other study findings showed a higher proportion of respondents who could mention severe vaginal bleeding as the danger sign in the intra-natal period. 16,32,34,36 However, a study conducted in Saudi Arabia, 25 Tanzania 27 and Uganda 37 showed the respondent's knowledge to be lesser than our study findings. The reason could be the perception of women that some amount of bleeding is normal during delivery.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…Many other study findings showed a higher proportion of respondents who could mention severe vaginal bleeding as the danger sign in the intra-natal period. 16,32,34,36 However, a study conducted in Saudi Arabia, 25 Tanzania 27 and Uganda 37 showed the respondent's knowledge to be lesser than our study findings. The reason could be the perception of women that some amount of bleeding is normal during delivery.…”
Section: Discussioncontrasting
confidence: 91%
“…33,29 Our study finding is lesser than the study findings of Saudi Arabia 25 and India 15 but higher than the study findings of Uganda 37 and different regions of Ethiopia. 16,23,26,32 In the present study, almost one fourth (24.2%) of the respondents mentioned severe headache as a danger signs during pregnancy which is similar to the study findings of Ethiopia 34 and India. 15 Contrast findings were found in many other studies conducted worldwide.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations